Effect of Broccoli (Brassica oleracea L. var. italica) Extract on Bleeding Time in Male White Mice (Mus musculus L.) - Suci Fitriani Sammulia; Almahdy Almahdy; Aldo Wahyu Rezky (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Cessation of bleeding is influenced by many factors including the type of medication used. The use of drugs to stop bleeding can be done in various ways, one of which is the use of traditional medicine. One of the traditional plants that can be used as a stop bleeding is broccoli (Brassica oleracea L. var. italica) which has a fairly high vitamin K content, where is efficacious as hemostatic. This study aims to determine the effect of broccoli on the bleeding time of mice tail cuts. The first group was negative control (Na-CMC), the second group was positive control (tranexamic acid), while groups three, four, and five were broccoli extract dose of 20, 40, and 60 mg/kg BW, respectively. All treatments were given orally for seven days. Bleeding time was calculated from the initial blood loss until the blood stopped (tail bleeding I method) and the data were analyzed with the ANOVA one way test and the post hoc Least Significant Difference (LSD) statistical test. The results showed that there were differences in the time to stop bleeding in the treatment control group at a dose of 20 mg/kg BW (122.60 ± 29.535 seconds), 40 mg/kg BW (102.40 ± 9.607 seconds) and 60 mg/kg BW (90.40 ± 3.845 seconds). From these results, it can be concluded that the extract of broccoli at a dose of 60 mg/kg BW gives the best results as hemostatic, while the effect is almost similar to the positive control group.